FRI0209 Recommendations for acquisition and considerations for interpretation of mri of the spine and sacroiliac joints in the investigation of axial spondyloarthritis in the uk. (12th June 2018) - Bray, T.; Jones, A.; Hall-Craggs, M.A.; Bennett, A.; Conaghan, P.G.; Grainger, A.; Hodgson, R.; Hutchinson, C.; Leandro, M.; Mandl, P.; McGonagle, D.; O'Connor, P.; et al.
Abstract : Background: The use of magnetic resonance imaging (MRI) has been instrumental in the early recognition and characterisation of axial spondyloarthritis (axSpA). However, a recent survey in the UK showed that there is diverse practice in the use of MRI and limited knowledge of MRI features suggestive of axSpA among radiologists. 1 Objectives: To develop clinical practice recommendations for the acquisition and interpretation of MRI of the spine and sacroiliac joints (SIJs) in the investigation of axSpA through a collaboration between rheumatologists and radiologists. Methods: A working group comprising 9 rheumatologists and 9 musculoskeletal radiologists with an interest in axSpA was established. The EULAR standardised operating procedures were followed. 2 Two working group meetings were held, the first to define the scope of the exercise and the second to review the results of the Systematic Literature Review that informed the recommendations. An anonymised Delphi process was used to formulate the final set of recommendations. The level of evidence and strength of recommendation was added to the recommendations. The level of agreement by working group members was assessed using a numerical rating scale. Results: A total of 2 overarching principles and 7 recommendations were formulated (figure 1). The first 3 recommendations address the MRI acquisition protocol, namely anatomical areas to be scanned and sequences to be used. The remaining 4 recommendations address the interpretation of active and structural lesions of the spine and SIJs. Conclusions: A UK joint rheumatology and radiology consensus on the most appropriate MRI acquisition protocol and interpretation of images in the investigation of axSpA was achieved. This consensus will help standardise practices and ensure prompt and effective patient management in the diagnosis and treatment of axSpA. References: [1] Bennett, et al. J Rheumatol2017. [2] van der Heijde, et al. Ann Rheum Dis2015. Acknowledgements: This work was financially supported by the British Society for Spondyloarthritis (BRITSpA). Disclosure of Interest: None declared